Estimated calving interval for the New Zealand southern right whale (Eubalaena australis). Issue 3 (3rd July 2018) - Davidson, Anthony Raphael; Rayment, William; Dawson, Steve M; Webster, Trudi; Slooten, Elisabeth
ABSTRACT: Southern right whales ( Eubalaena australis ) were widespread in New Zealand waters before commercial whaling in the nineteenth century caused drastic declines in their abundance and distribution. Following the cessation of whaling, the population has been recovering and is now slowly recolonising its former range. Estimates of population demographics, including reproductive output, are essential for predicting the trajectory of this population. We gathered photo-identification data on female southern right whales during annual field trips to the Auckland Islands, the principal calving area in New Zealand waters. Forty-five calving intervals were observed between 2006 and 2013 (mean interval = 3.31 years, 95% CI = 3.06–3.57). Incorporating the effects of possible missed calving events produced a plausible range of mean calving intervals from 3.17 to 3.31 years. Our results suggest that the calving interval of New Zealand southern right whales is similar to that found in populations elsewhere.